Oxidative potential of ambient fine aerosol over a semi-urban site in the Indo-Gangetic Plain. (February 2018) - Patel, Anil; Rastogi, Neeraj
Abstract: Indo-Gangetic Plain (IGP) receives emissions from variety of pollutant sources such as post-harvest crop residue burning, vehicles, industries, power plants, and bio-fuel burning. Several studies have documented physical, chemical and optical properties of aerosol over the IGP; however, their oxidative potential (OP) has not yet documented. Present study reports the OP (measured through dithiothreitol (DTT) assay) of soluble particulate matter smaller than 2.5 μm aerodynamic diameter (PM2.5 ) over Patiala (30.3°N, 76.4°E, 249 m amsl), a semi-urban site located in the IGP, during winter 2014. Volume-normalized OP (range: 1.3–7.2 nmol DTT min −1 m −3, average: 3.8 ± 1.4, 1σ) is found to be ∼3 to 20 times higher, and mass-normalized OP (range: 13-50 pmol DTT min −1 μg −1, average: 27 ± 8, 1σ) is found to be similar or higher than those documented in literature. Further, observed OP is found to depend more on PM2.5 composition rather than mass concentration. Mass fractions of organic carbon (OC), elemental carbon (EC) and water-soluble organic carbon (WSOC) correlate positively whereas that of secondary inorganic aerosol (SIA, sum of the concentrations of SO 4 2 −, NO 3 − and NH 4 + ) correlate negatively with OP μg −1 at considerable significance level (p < 0.05). Negative correlation of SIA with OP μg −1 has been assessed in laboratory experiment and attributed to their DTT inactive nature. It is suggested to use WSOC/SIA ratio as a measure of DTT activity of secondary particles over the study region. Further, biomass burning derived species are observed to be more DTT active than those derived from fossil fuel burning. It was also observed that the slope of OP μg −1 and WSOC/SIA ratio linear relationship enhances significantly in samples collected during days following foggy nights in comparison to that in samples collected during non-foggy period, which may be due to the production of redox-active species by fog processing. Such studies have implications in assessing the effect of ambient aerosol on atmospheric chemistry, air quality and human health. Highlights: First study on oxidative potential (OP) of aerosol over the Indo-Gangetic Plain. Secondary organics appear to enhance aerosol OP. Secondary inorganics are DTT inactive. Fog processing of secondary organics may enhance their DTT activity.